The Life of A Miner - Kalman, Bobbie; Calder, Kate 1974- (New York : Crabtree Pub. Co., 2000)
Describes the hard rock mining industry that developed in the American west following the gold rush, including the operations of a mine and the lives of the miners and their families.
Includes index.
Keywords: Gold miners -- History -- West (U.S.); Gold miners -- History -- Canada, Western; Gold mines and mining -- History -- West (U.S.); Gold mines and mining -- History -- Canada, Western